Study on the Morphology of Fasciola gigantica and Economic Losses due to Fasciolosis in Berau, East Kalimantan - Muhammad Rofi' Prasetya; Setiawan Koesdarto; Nunuk Dyah Retno Lastuti; Lucia Tri Suwanti; Kusnoto Kusnoto; Muchammad Yunus (Biosaintifika: Journal of Biology & Biology Education, 2019)
Fasciolosis is one of the endemic parasitic diseases in Indonesia and causes significant economic losses. Fasciola gigantica is the main species found to infect livestock. This research aimed to describe the morphology of F. gigantica histologically using hematoxylin and eosin staining as well as ultrastructure morphology using scanning electron microscopy (SEM). Besides, the study was also carried out to determine the prevalence and estimation of economic losses due to fasciolosis in Berau Regency. The histological identification of flukes morphology found several organs including oral sucker (OS), ventral sucker (VS), cirrus (C), genital pore (GP), uterus (U), ovary (O), tegument (Te), testis (T), and caecum (C). In this study, ultrastructure morphology was divided into anterior and midbody region. In the anterior region, there are an oral sucker (OS) with a diameter of 304.5 µm and a ventral sucker (VS) with a diameter of 571 µm. It was also found the anterior spine with a width of 25.4 µm and a height of 22.8 µm. In the midbody, the spine has a width of ± 26.7 µm and a length of ± 38.9 µm leading posteriorly. Postmortem examination results showed that the prevalence of fasciolosis in Berau regency was 21.65% or 34 of 157 cows which were positive with an estimated loss of 228,656,475.00 IDR/16,450 USD (1 USD=13,900 IDR). The amount of loss due to fasciolosis must be a particular concern in carrying out control and prevention measures. Histology and ultrastructure morphology can become a reference in the development of anthelmintic testing that has been used so far in Indonesia.